Learning anatomy during COVID pandemic: a study from Universal College of Medical Science - Sharma, Nitasha; Pandit, Ruku (Journal of Chitwan Medical College, 2021)
Background: Pandemic plays a pivotal role in reshaping history of mankind. Forced disruption in anatomy education system has compelled us to start all our classes online. Although the COVID‐19 pandemic is likely to be the first which current anatomy students are affected by, lessons and experiences can be drawn from the present crises to help us adapt and reform anatomy. The aim of this study was to evaluate medical students’ experience about learning anatomy online during covid pandemic.Methods: This was a descriptive cross-sectional study carried out at universal college of medical science among first and second year MBBS and BDS students from 1st June 2020 to 30th August 2020. A semi-structured, validated, feedback questionnaire was emailed to a total of 255 students, and the filled up response was received from 211 students. The data were collected and descriptive analysis was done using SPSS ver. 22.Results: Almost 178(84.36%) of students were understanding anatomy class through online lectures, Majority of students 196 (92.89%) of students consider dissection/cadavers or models as an integral part for learning anatomy. similarly, more than three fourth 168(79.62%) of students were in favor of combination of online class with traditional class for better understanding of anatomy discipline.Conclusions: Online anatomy class was considered effective during crisis but students were suggesting blending of online class with traditional class. Lesson should be learned from current pandemic and explore anatomy education system beyond traditional. We highly recommend development of new anatomy blended curriculum for better understanding of subject.